The intensification of consecutive three tropical cyclones passing over a warm ocean eddy in the South China Sea - Luo, Xi; Yang, Wei; Yang, Lei; Wang, Dongxiao (Frontiers in Climate, 2022)
An extremely strong and long-lasting (more than 8 months) oceanic warm core eddy existed in the South China Sea (SCS) from February–October 2010. From July–August 2010, three tropical cyclones (TCs; TC Conson, Chanthu, and Mindulle) consecutively passed over this eddy and sustained at least 21 h. The intensity change of all three TCs reached 20 kt within 24 h when they encountered this eddy. In mid-late July, tropical cyclone heat potential (TCHP) is overall stronger in the eddy region than in its surrounding region, thus TCHP plays an important role in the intensification of TC Conson and Chanthu. It is also found that the intraseasonal oscillation (ISO) and the quasi-biweekly oscillation (QBWO) can be important in favor of the further enhancement of TCs. The TCHP is too low to favor the intensity increase of TC Mindulle in late August, 2010, but weak vertical wind shear, ISO and QBWO act as key roles in the intensification of TC Mindulle.